When gender research hit home: The importance of gender in research - Randolph, Thomas F. (International Livestock Research Institute, 2016)
Looking back 20 years, Tom Randolph recalls a moment which influenced his priorities in gender and research. In tests of new varieties of short rice with men and women in West Africa, the men were delighted by the varieties’ high-yielding potential. Women, on the other hand, said they would never sow such varieties because harvesting such short plants would break their backs. It was clear that just looking at technology improvements was not enough. While much progress has been made, smarter solutions are still needed in Livestock and Fish projects. Interview with Thomas F. Randolph (CGIAR Research Program on Livestock and Fish) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684